顎関節症診断に対する歯科用小照射野Ｘ線ＣＴ（Ｏｒｔｈｏ‐ＣＴ）の有用性について 第２報 多断面における骨形態観察 - SAWADA Kunihiko; HONDA Kazuya; ARAI Yoshinori; TAKANO Yumi; KASHIMA Masahiro; IWAI Kazuo; HASHIMOTO Koji; SHINODA Koji (Journal of the Japanese Society for the Temporomandibular Joint, 2002)
The aim of the study was to assess the capability of hypocycloidal tomography and Orthocubic super-high-resolution CT (Ortho-CT) comparing osseous structures' change in many sections (lateral part, central part, medial part) of the temporomandibular joint (TMJ).This method was applied to 60 TMJs of 30 TMJ disorder patients. The subjects were 4 males and 26 females (mean age, 30.8 years). We used hypocycloidal tomography, which corresponds to the center of the condyle, and this part image was made into the center of the fossa and the condyle. The 2nd section of the lateral was made into the lateral tomogram from there, and the 2nd section of the medial side was made into the medial side tomogram. We selected an Ortho-CT image identical to three levels of tomogram and compared their Ortho-CT 180 images. Examination method was classified as mandibular fossa and condyle head, and it was classified into osseous abnormalities and normal bone structure. Ortho-CT has a high degree of concordance with tomography, and as for osseous abnormalities, Ortho-CT was observed rather than the hypocycloidal tomography in all tomographic part.These results suggest that Ortho-CT is more sensitive for osseous abnormalities than conventional tomography, and therefore seems to be a better alternative to conventional tomography to evaluate osseous abnormalities of the TMJ. この研究の目的は, 顎関節の多断面 (外側部, 中央部, 内側部) の骨形態変化を単純断層とOrthocubic super high resolution CT (以下Ortho-CTと略す) で比較し, その検出能を調べることである。症例は単純断層X線検査とOrtho-CT検査を施行した30例60関節である。内訳は女性26例52関節, 男性4例8関節, 平均年齢30.8歳である。資料は単純断層X線写真における下顎頭の中央に相当する断層X線写真を用い, これを下顎頭および下顎窩の中央断層像とした。その中央断層面から外側2層目を外側断層像, 内側2層目を内側断層像とした。それら3層の断層像と相対するOrtho-CT像を選択し, 単純断層180像とOrtho-CT180画像を比較した。検討方法は顎関節部を下顎窩と下顎頭に分類し, 骨変化ありと骨変化なしに分類した。下顎窩および下顎頭ともに, Ortho-CTと単純断層の一致率は高く, また外側部, 中央部, 内側部のすべてにおいてOrtho-CTのほうに「変化あり」が多く観察された。以上の結果より, Ortho-CTのほうが, 従来の単純断層より, 骨の形態変化の評価に優れており, 単純断層に代わり, 有用性が高いことが示唆された。